Tinjauan Yuridis Terhadap Pembatalan Perjanjian Perkawinan: (Studi Kasus Putusan Perkara Nomor 598 PK/Pdt/2016) - Syaputra, Didi (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This research aims to analyze and criticize the substance of the annulment of marriage agreements (Case Study of the Decision in Case Number 598 PK/Pdt/2016) and the judge's considerations in handing down the decision in case Number 598 PK/Pdt/2016. This research uses normative legal research methods or library legal research. The nature of the research is descriptive analytical. This type of research uses secondary data obtained from primary legal materials, secondary legal materials and tertiary legal materials. Data analysis uses qualitative analysis. The results of the research show that the judicial review of the annulment of the marriage agreement (Case Study of Case Decision Number 598 PK/Pdt/2016) which in its decision annulled the Cassation Decision Number 503 K/Pdt/2015 and declared the Marriage Agreement Deed Number 200 dated July 8 1994 between the Petitioners null and void. Judicial Review with the Respondent Judicial Review is a correct and appropriate decision and should be carried out, referring to the formality of making a deed which is not in accordance with the provisions of Article 29 of the Marriage Law. The legal consideration of the Panel of Judges in handing down its decision was because the previous judge's interpretation of the provisions of Article 29 paragraph (1) of the Marriage Law, that a marriage agreement executed before a Notary had met the formal requirements was too broad, thus changing the meaning of the article. The judge seemed to equate an "agreement" in general with a "marriage agreement", even though the provisions of this article are imperative (must be implemented).